From "Sacrilege" to Sustainability : Reforestation and Organic Farming in Forikrom, Ghana - Easton, Peter (World Bank, Washington, DC, 2012)
Forikrom, a community of 6,000 people in the Techiman District of Ghana, is located in an area of open grassland. The area once produced cocoa, but the practice ended in 1983 after some fires. Further deforestation resulted from inappropriate farming methods. Forikrom has now turned the corner to reforestation of its environment, but the initiative did not succeed without significant cultural conflict and could have reached the level it has without the impetus for new solutions that the conflict produced. The most important consequences of the Forikrom initiative have been: a) social comity and b) the emergence of an environmentally-conscious community that serves as a model for other towns in the region.